Design and development of an interactive monitoring system for Pilgrims in congregation of hajj ritual - Mantoro, Teddy; Akhtaruzzaman, M; Mahmud, Murni; Ayu, Media (2015)
This paper represents an interactive and cost effective monitoring system for positioning and localization of Hajj Pilgrims during Hajj Ritual. The system circumscribes three major areas from the customer perspectives and accumulates together as an integrated and interactive monitoring system to apply in pervasive conglomerating environment during Hajj. During the holy activity a huge number of people gather together and missing pilgrims, locating lost, injury, health problem etc. are repeatedly encountered. These situations create sorrowfulness in their relatives’ minds as well as the responsible Hajj committee members. To reduce these problems and also to provide helps to the pilgrims, this paper presents a panoptic view of the proposed Hajj Pilgrims Monitoring System with its architecture, design and implementation techniques. The architecture is designed based on two major sections, one: the uses of smart phones as a common platform with a connection server for active pilgrims, and two: the monitoring system with database server. Again the monitoring system is designed to provide support for both of the passive users, the administrative users of Hajj committee and the general people all over the world. The paper also represents some experimented and comparative results to establish the reliability, usability, user friendliness, and easy to use of the interactive monitoring system.